Pentingnya Layanan Khusus di Sekolah dalam Menunjang Pembelajaran Peserta Didik - Akbar Rafsanjani; Ari Wibowo Sembiring; Era Yunita; Zuchairunnisa Zuchairunnisa (Departement of Mathematics Education, 2023)
Management of special services in a school is an important part of School Based Management (SBM). School is one means that can be used to improve the quality of the Indonesian nation. Schools do not only have responsibilities and duties to carry out the learning process in developing science and technology, but must maintain and improve the physical and spiritual health of students. Therefore schools need a special service management that can manage all the needs of their students so that these educational goals can be achieved. Students are a core element of educational activities. In the era of competition between educational institutions that is so tight as it is today, schools must fight seriously to get students. There are even heads of educational foundations who say that finding students is far more difficult than finding new teachers. Student management is not only in the form of recording student data, but includes broader aspects operationally that can help efforts to grow and develop students through the educational process at school.